The influence of the static and dynamic characteristics of power sources on the behaviour of short circuiting CO2 shielded welding arcs - Pierozeck, B. S. (College of Aeronautics, 1965)
The work discussed in this report has examined, oscillographically, the influence of variable slope and variable inductance on the characteristics of short circuiting CO2 shielded metal arcs, and the variables affecting the optimum welding conditions have been determined. It has been established th9.t this optimum is usually below the maximum of the frequency voltage curve. Both the slope of the power source characteristic and the value of the inductance in the circuit have similar qualitative effects on the stability of the short circuiting arc. Nevertheless, control of the dynamic response by varying inductance has been found to be more flexible and effective. For this reason, it is suggested that separate control of the static characteristic and dynamic response is not necessary to obtain optimum conditions. Thus the correctly designed power source for short circuiting CO2 shielded arc welding should have constant slope of the static characteristic and continuous control of the dynamic response.